2005
DOI: 10.1111/j.1600-6143.2005.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bleeding After Islet Transplantation: Lessons Learned from a Multivariate Analysis of 132 Cases at a Single Institution

Abstract: Islet transplantation is being offered increasingly for selected patients with unstable type 1 diabetes. Percutaneous transhepatic portal access avoids a need for surgery, but is associated with potential risk of bleeding. Between 1999 and 2005, we performed 132 percutaneous transhepatic islet transplants in 67 patients. We encountered bleeding in 18/132 cases (13.6%). In univariate analysis, the risk of bleeding in the absence of effective track ablation was associated with an increasing number of procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 28 publications
1
85
0
Order By: Relevance
“…3,[16][17][18] However, it is difficult to apply these anticoagulants in the clinical environment because systemic administration is associated with an increased risk of severe bleeding. 19 Therefore, there is an urgent need to explore new therapeutic target for treating IBMIR with fewer bleeding complications. The present study shows that TAFI is activated and accumulated during the first hour after islet infusion, indicating that TAFIa is sufficient to affect fibrinolysis in IBMIR.…”
Section: Discussionmentioning
confidence: 99%
“…3,[16][17][18] However, it is difficult to apply these anticoagulants in the clinical environment because systemic administration is associated with an increased risk of severe bleeding. 19 Therefore, there is an urgent need to explore new therapeutic target for treating IBMIR with fewer bleeding complications. The present study shows that TAFI is activated and accumulated during the first hour after islet infusion, indicating that TAFIa is sufficient to affect fibrinolysis in IBMIR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is our hypothesis that the development complement, and suppressed neutrophil infiltration. In (38). Several other strategies to prevent or suppress IBMIR have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…They also further investigated whether partial portal thrombosis was associated with detrimental loss of islet functional reserve. The incidence of portal thrombosis was low (3.2 %); despite partial portal thrombosis there was no detectable loss of islet graft function as measured by the SUITO index or insulin requirements [13,14]. Furthermore, Bucher et al [15] reported no association between portal thrombosis and increased IP pressure in islet autograft and allogeneic transplants when they limited the tissue volume infused to a mean of 13 cc [15].…”
mentioning
confidence: 98%